Media Power and Democratization in Brazil: TV Globo and the Dilemmas of Political Accountability - Porto, Mauro (Taylor & Francis, 2012)
This book analyzes the relationship between media power and democratization in transitional societies based on a case study about TV Globo, Brazil's largest media group.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); Brésil (corpus analysé); Brésil (lieu de production du savoir); _Nettoyé